Tungsten modified C / C composite material and preparation method thereof

By suctioning the tungsten powder on the surface of the C/C composite material and fixing the W powder through chemical vapor penetration, the problems of easy oxidation of the C/C composite material and easy falling off in high temperature environments are solved, which significantly improves the material's ablation resistance and binding strength.

CN119504281AActive Publication Date: 2025-02-25NORTHWESTERN POLYTECHNICAL UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411729066.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-25
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

The existing C/C composite materials are prone to oxidation under high temperature environments, resulting in low ablation resistance, and the W coating is prone to fall off and oxidation during spraying, affecting the binding strength.

Method used

By placing the C/C composite material on the filter membrane, the suspension of tungsten powder is suction filtered to form a first composite structure in which tungsten powder and C/C composite material is composited, and the W powder is fixed inside the C/C composite material through a chemical vapor-phase penetration process and densified.

Benefits of technology

The W is serrated at the interface of the C/C composite material, which significantly enhances the bonding force between the coating and the substrate and improves the ablation resistance of the material. At the same time, the process is simple and the cost is low, and it is suitable for components with complex shapes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119504281A_ABST
    Figure CN119504281A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of preparation of carbon fiber reinforced carbon-based composite materials, and discloses a tungsten modified C / C composite material and a preparation method thereof.The C / C composite material is placed on a filter membrane, suction filtration is conducted on turbid liquid of tungsten powder, a first composite structure formed by compositing the tungsten powder and the C / C composite material is obtained, and the first composite structure is dried; and performing carbon deposition densification on the dried first composite structure to obtain the tungsten modified C / C composite material. The tungsten is distributed in a zigzag shape at the interface of the coating and the substrate, so that the binding force between the coating and the substrate is obviously enhanced. In the initial stage of ablation, the coating tungsten transfers heat on the surface of the composite material to the matrix, and then the matrix tungsten transfers the heat into the material, so that concentrated thermal stress on the surface of the material is reduced. Along with gradual increase of the temperature, the matrix tungsten firstly chemically reacts with C to strongly absorb heat, and WO3 formed by surface oxidation evaporates to absorb heat, so that the heating rate and the ablation temperature of the surface of the composite material are reduced, and the ablation resistance of the material can be powerfully improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of carbon fiber reinforced carbon-based composite materials, and specifically relates to a tungsten-modified C / C composite material and a preparation method thereof. Background Art

[0002] Carbon / carbon (C / C) composites have the advantages of low density, low thermal expansion coefficient, high specific strength, and excellent high-temperature mechanical properties. They are ideal high-temperature structural materials in inert environments. However, C / C composites will oxidize in an aerobic environment at 370°C. When the temperature exceeds 500°C, the oxidation rate increases rapidly, which seriously degrades the high-temperature performance of C / C composites. At present, coating technology and matrix modification are effective ways to improve the anti-oxidation / ablation properties of C / C composites. W has a melting point of up to 3422°C and has excellent properties such as high modulus and low thermal expansion coefficient. It has been used as a key throat lining material for solid rocket engines. However, the density of the W throat lining is as high as 19.35 g / cm 3 , it is difficult to meet the requirements of light weight for high-speed flight vehicles. At present, throat lining materials basically use C / C composite materials with lower density. However, in terms of ablation resistance, C / C composite throat linings are still inferior to W throat linings. Reference 1 "[1] Xie Huizhen, Li Ruizhen, Cui Hong, et al. Research on plasma spraying of tungsten-based materials and thin-walled components [J]. Solid Rocket Technology, 2012, 35 (06): 812-815+820." W-based thin-walled components were prepared by atmospheric plasma spraying. The hot test was conducted for 6.4 s at a temperature of about 3000℃ and an average pressure of 3.2 MPa. There was no sign of ablation on the surface of the throat material. This provides a new idea for improving the ablation resistance of C / C composite materials. W is used to modify C / C composite materials, giving full play to the advantages of both, and obtaining a lightweight and ablation-resistant composite material.

[0003] Document 2 "Zhou, Z., Wang, Y., Gong, J. et al. Ablation Resistance of C / CComposites with Atmospheric Plasma-Sprayed W Coating. J Therm Spray Tech25, 1657-1665 (2016). "A 1.2 mm thick W coating was sprayed on the surface of a C / C composite by atmospheric pressure plasma spraying (APS). After 150 s of oxyacetylene flame ablation, the linear ablation rate of the obtained composite material was reduced by 23.55% compared with the Zr / Cu infiltrated C / C composite material. APS can quickly prepare the W coating, but during the spraying process, the coating surface is easily oxidized to form loose and porous tungsten oxide. At the same time, the coating is also prone to generate large residual stress, which will reduce the bonding strength between the W coating and the substrate and cause the coating surface to warp and crack.

[0004] Therefore, if W is used to modify C / C composites and the disadvantage of easy peeling and oxidation of W coating sprayed on the surface of C / C composites is avoided, it is urgent to find a new method to introduce metal W into C / C composites to improve their ablation resistance. Summary of the invention

[0005] In view of the shortcomings of the prior art, the object of the present invention is to provide a tungsten-modified C / C composite material and a preparation method thereof, so as to prepare a lightweight, ablation-resistant composite material.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: A method for preparing a tungsten-modified C / C composite material comprises the following steps: The C / C composite material is placed on a filter membrane, and the suspension of tungsten powder is filtered to obtain a first composite structure of tungsten powder and the C / C composite material, and the first composite structure is dried; The dried first composite structure is subjected to carbon deposition densification to obtain a tungsten-modified C / C composite material.

[0007] Preferably, during the filtration, each filtration process is performed until no more suspension can be drawn into the surface of the C / C composite material, and then drying is performed.

[0008] Preferably, the method for preparing the tungsten-modified C / C composite material further includes the following process: The process of placing the dried first composite structure on the filter membrane, filtering the suspension of tungsten powder and drying the first composite structure is repeated until the first composite structure no longer increases in weight.

[0009] Preferably, before drying the first composite structure composed of tungsten powder and C / C composite material, the remaining powder on the surface of the first composite structure is washed away with anhydrous ethanol, and then drying is performed.

[0010] Preferably, during the filtration, the web layers and the non-woven fabric layers of the C / C composite material are arranged alternately with the surface facing upward.

[0011] Preferably, in the suspension of tungsten powder, the solvent is anhydrous ethanol, and the mass ratio of tungsten powder to anhydrous ethanol is 1:(3-4). When the first composite structure is dried, the drying temperature is 70-80°C and the drying time is 10-12 h.

[0012] Preferably, the particle size of the tungsten powder is 3-5 μm, and the density of the C / C composite material is 1.0-1.3 g / cm 3 .

[0013] Preferably, the preparation method of the tungsten modified C / C composite material further comprises the following steps: firstly washing and pretreating the C / C composite material, and then filtering the washed and pretreated C / C composite material; When the C / C composite material is subjected to cleaning pretreatment, the C / C composite material is subjected to ultrasonic cleaning and then dried at 60-80° C. for 10-12 hours.

[0014] Preferably, the process of performing carbon deposition densification on the dried first composite structure comprises: In a protective atmosphere, using methane gas, vapor-depositing pyrolytic carbon on the surface of the dried first composite structure to achieve carbon deposition and densification of the first composite structure; The temperature during vapor deposition of pyrolytic carbon is 1030-1070°C for 20-30 hours. After the deposition is completed, the temperature is first lowered to 300°C and then cooled with the furnace.

[0015] The present invention also provides a tungsten modified C / C composite material, which is prepared by the preparation method of the present invention as described above.

[0016] Compared with the prior art, the present invention has the following beneficial effects: The present invention uses tungsten powder and anhydrous ethanol as raw materials, introduces tungsten into the surface layer of the C / C composite material through a vacuum filtration process, and then fixes the W powder inside the C / C composite material through a chemical vapor infiltration process, and densifies the composite material. In the tungsten-modified C / C composite material prepared by the preparation method of the present invention, W is distributed in a zigzag shape at the interface between the coating and the substrate, and this structure significantly enhances the bonding force between the coating and the substrate. Metal W has excellent thermal conductivity. In the early stage of ablation, the coating W transfers the heat on the surface of the composite material to the substrate, and the substrate W then transfers the heat to the interior of the material, reducing the thermal stress concentrated on the surface of the material. As the temperature gradually increases, the substrate W first reacts chemically with C to strongly absorb heat, and the surface oxidation forms WO 3 Evaporation absorbs heat, which reduces the heating rate and ablation temperature of the composite material surface, and can effectively improve the ablation resistance of the material. In addition, the preparation process of the present invention is simple, the cycle is short, the cost is low, and components with complex shapes can be prepared, which has great development potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 The present invention is a flow chart of the method for preparing the tungsten modified C / C composite material.

[0018] FIG2( a ) is a surface morphology image (low-magnification image) of the low-density carbon-carbon composite material after filtration W in Example 1 of the present invention; FIG2( b ) is a surface morphology image of the low-density carbon-carbon composite material after filtration W in Example 1 of the present invention.

[0019] FIG3( a ) is a cross-sectional backscattering image (high magnification image) of the C / CW composite material of Example 1 of the present invention; FIG3( b ) is a cross-sectional backscattering image (low magnification image) of the C / CW composite material of Example 1 of the present invention.

[0020] Figure 4 This is a curve of the change of the surface temperature of the sample when the C / CW composite material is subjected to an ablation test for 60 s in Example 1 of the present invention.

[0021] Figure 5 It is a cross-sectional SEM image of the composite material obtained in Comparative Example 1 of the present invention.

[0022] Figure 6 This is the XRD diagram of the composite material obtained in Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0023] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention. If no specific conditions are specified in the embodiments, they are carried out under conventional conditions or conditions recommended by the manufacturer. Herein, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are only for simplicity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be deemed to have covered and specifically disclosed all possible secondary ranges and individual values ​​(including integers and fractions) within the range.

[0024] Reference Figure 1 The preparation method of the tungsten modified C / C composite material of the present invention comprises the following steps: S1: Mix anhydrous ethanol and 3-5 μm W powder into a slurry. The mass ratio of W powder to anhydrous ethanol is 1:(3-4). Add a stirring bar and stir under a magnetic stirrer for 1-2 h to form a suspension. S2: Density 1.0-1.3 g / cm 3 The C / C composite material was processed into a φ28 mm×8 mm specimen, the surface of which was polished with a grinding disc and then ultrasonically cleaned, and then placed in a 70-80℃ oven to dry for 10-12 h; S3: Take a 50 mm organic filter membrane with a pore size of 0.1 μm, moisten it with alcohol, and place it flat on the sand core filter so that the filter membrane fits tightly with the filter. Place the sample (i.e., C / C composite material) (with the xy surface (i.e., the surface where the mesh layer and the non-woven fabric layer are alternately distributed) facing up) on the filter membrane, cover it with a cylindrical glass funnel, and fix the device with an aluminum alloy clip. After the device is fixed, turn on the vacuum pump and drip anhydrous ethanol to check whether the vacuum pump can be used normally. Use a dropper to draw the slurry and drip it evenly on the surface of the sample. The internal and external pressure difference formed by the vacuum pump squeezes out the anhydrous ethanol inside the sample, and the W powder remains inside the sample. Repeat this operation until the W powder cannot be drawn into the surface of the sample. During this period, stir the slurry continuously to prevent powder deposition. Take out the sample, rinse off the residual powder on the surface with anhydrous ethanol, put it in a 70-80℃ oven to dry for 10-12 hours, and then weigh it.

[0025] S4: Repeat step S3 until the weight gain of the dried sample is no longer obvious.

[0026] S5: Fix the composite material obtained in S4 in the mold of a small chemical vapor deposition furnace. Place the mold in the furnace and evacuate it to a pressure below -0.01 MPa. Introduce Ar gas as a protective gas and set the flow rate to 1 L / min. Heat up to 1030-1070°C at a heating rate of 5-8°C / min. Then introduce methane, set the methane flow rate to 0.6 L / min, set the argon flow rate to 2.4 L / min, and the methane to argon flow ratio is 1:4. After keeping warm for 20-30 h, cool down to 300°C and cool with the furnace to obtain a dense C / CW composite material. Through the chemical vapor infiltration process, the densification of the W coating on the surface of the composite material is achieved, and the C / CW composite material is densified at the same time, so as to obtain a composite material integrating W coating and modified C / C.

[0027] Through the above scheme of the present invention, W is distributed in a zigzag shape at the interface of the obtained C / CW composite material. This structure significantly enhances the bonding force between the coating and the substrate. During the ablation process, metal W can maintain the surface temperature of the C / C composite material stable at 1170-1200°C for nearly 10 s due to its good thermal conductivity and the fact that it absorbs a lot of heat during the carbonization reaction. At the same time, WO generated by oxidation during the ablation process 3 Evaporation and heat absorption occur above 1800°C, thereby slowing down the rate of increase in the surface temperature of the sample, which significantly improves the ablation resistance of the C / C composite material. The composite material prepared by the present invention also has the advantages of simple process, low cost, short cycle, etc.

[0028] Embodiment 1: The preparation method of the tungsten modified C / C composite material in this embodiment includes the following steps: S1: Weigh W powder and anhydrous ethanol in a weight ratio of 1:3 into a beaker and stir with a magnetic stirrer at room temperature for 2 h to form a suspension; S2: The density is 1.3 g / cm 3 The C / C composites were cleaned by ultrasonic cleaning and dried in an oven at 70 °C for 12 h; S3: Build a vacuum filtration device and place the dried sample of S2 (xy side facing up) on the filter membrane. Use a dropper to extract the slurry and drip it onto the surface of the sample, controlling the powder to be evenly distributed on the surface. Continue until no more W powder can be drawn onto the surface. Remove the sample, rinse off the remaining powder on the surface with anhydrous ethanol, and dry it in an oven at 70°C for 12 h before weighing it.

[0029] S4: Repeat step S3 until the weight gain of the sample is no longer obvious. Figure 2 (a) is a high-magnification image of the surface of the C / C composite material of this embodiment after the W powder is filtered out. It can be seen that the 3-5 μm W powder is closely distributed around the carbon fiber. Figure 2 (b) is a low-magnification image of the surface of the carbon-carbon composite material of this embodiment after the W powder is filtered out. It can be seen that the W powder is mainly distributed in the mesh layer, and the non-weft cloth layer is less distributed.

[0030] S5: Fix the composite material obtained in S4 in the mold of a small chemical vapor deposition furnace. Place the mold in the furnace and evacuate it to a pressure below -0.01 MPa. Introduce Ar gas as a protective gas and set the flow rate to 1 L / min. Raise the temperature to 1070°C at a heating rate of 5-8°C / min. Then introduce methane with a flow rate of 0.6 L / min, and argon with a flow rate of 2.4 L / min. The ratio of methane to argon is 1:4. After keeping warm for 20 hours, cool with the furnace to obtain a dense C / CW composite material with a porosity of 20.19%. Figure 3 (a) is a low-magnification cross-sectional backscattering image of the C / CW composite material in this embodiment. It can be seen that there is a W coating with a thickness of 100 μm on the surface of the composite material. The maximum depth of W in the web layer is 400 μm, and the overall structure is serrated. The W coating tightly grasps the C / CW matrix, which effectively enhances the bonding force between the coating and the matrix, achieving the effect of W on the integrated modification of the matrix-coating of the C / C composite material. Figure 3 (b) is a high-magnification cross-sectional backscattering image of the C / CW composite material in this embodiment. The white phase in the figure is W. During the densification process of the composite material, W is basically not carbonized or oxidized. The pyrolytic carbon deposited during the chemical vapor infiltration process tightly fixes the W powder around the carbon fiber. Figure 4 This is the curve of the sample surface temperature change during the low-power ablation of the C / CW composite material in this example. It can be seen that there is an obvious platform area at 1180°C. In this temperature range, W and C react violently and absorb heat, so that the temperature of the sample surface remains stable for a period of time. After 1800°C, the increase rate of the sample surface temperature slows down. This is due to the WO formed by surface oxidation.3 The effect of evaporation and heat absorption. These buffer the thermal stress on the sample during the ablation process and improve its ablation resistance.

[0031] Embodiment 2: The preparation method of the tungsten modified C / C composite material in this embodiment includes the following steps: S1: Weigh W powder and anhydrous ethanol in a weight ratio of 1:3 into a beaker and stir with a magnetic stirrer at room temperature for 1 h to form a suspension; S2: The density is 1.0 g / cm 3 The C / C composite material was cleaned by ultrasonic cleaning and dried in a 70 °C oven for 10 h; S3: Build a vacuum filtration device and place the dried sample of S2 (xy side facing up) on the filter membrane. Use a pipette to extract the slurry and drip it onto the surface of the sample, controlling the powder to be evenly distributed on the surface. Continue until no more W powder can be drawn onto the surface. Remove the sample, rinse off the remaining powder on the surface with anhydrous ethanol, and dry it in an oven at 70°C for 10 h before weighing it.

[0032] S4: Repeat step S3 until the weight gain of the sample is no longer obvious.

[0033] S5: Fix the composite material obtained in S4 in the mold of a small chemical vapor deposition furnace. Place the mold in the furnace and evacuate the furnace to a pressure below -0.01 MPa. Introduce Ar gas as a protective gas and set the flow rate to 1 L / min. Raise the temperature to 1060°C at a heating rate of 5-8°C / min. Then introduce methane and set the flow rate to 0.6 L / min, and the argon flow rate to 2.4 L / min. The ratio of methane to argon flow is 1:4. After keeping warm for 20 hours, cool with the furnace to obtain a dense C / CW composite material with a porosity of 24.66%.

[0034] Embodiment 3: The preparation method of the tungsten modified C / C composite material in this embodiment includes the following steps: S1: Weigh W powder and anhydrous ethanol in a weight ratio of 1:4 and place them in a beaker. Stir with a magnetic stirrer at room temperature for 2 h to form a suspension. S2: The density is 1.1 g / cm 3 The C / C composite material was cleaned by ultrasonic cleaning and dried in a 70 °C oven for 10 h; S3: Build a vacuum filtration device and place the dried sample of S2 (xy side facing up) on the filter membrane. Use a pipette to extract the slurry and drip it onto the surface of the sample, controlling the powder to be evenly distributed on the surface. Continue until no more W powder can be drawn onto the surface. Remove the sample, rinse off the remaining powder on the surface with anhydrous ethanol, and dry it in an oven at 80°C for 10 h before weighing it.

[0035] S4: Repeat step S3 until the weight gain of the sample is no longer obvious.

[0036] S5: Fix the composite material obtained in S4 in the mold of a small chemical vapor deposition furnace. Place the mold in the furnace and evacuate the furnace to a pressure below -0.01 MPa. Introduce Ar gas as a protective gas and set the flow rate to 1 L / min. Raise the temperature to 1070°C at a heating rate of 5-8°C / min. Then introduce methane with a flow rate of 0.6 L / min, and argon with a flow rate of 2.4 L / min. The ratio of methane to argon is 1:4. After keeping warm for 30 hours, cool with the furnace to obtain a dense C / CW composite material with a porosity of 23.07%.

[0037] Embodiment 4: The preparation method of the tungsten modified C / C composite material in this embodiment includes the following steps: S1: Weigh W powder and anhydrous ethanol in a weight ratio of 1:4 and place them in a beaker. Stir with a magnetic stirrer at room temperature for 2 h to form a suspension. S2: The density is 1.3 g / cm 3 The C / C composite material was cleaned by ultrasonic cleaning and dried in a 70 °C oven for 10 h; S3: Build a vacuum filtration device and place the dried sample of S2 (xy side facing up) on the filter membrane. Use a pipette to extract the slurry and drip it onto the surface of the sample, controlling the powder to be evenly distributed on the surface. Continue until no more W powder can be drawn onto the surface. Remove the sample, rinse off the remaining powder on the surface with anhydrous ethanol, and dry it in an oven at 70°C for 12 h before weighing it.

[0038] S4: Repeat step S3 until the weight gain of the sample is no longer obvious.

[0039] S5: Fix the composite material obtained in S4 in the mold of a small chemical vapor deposition furnace. Place the mold in the furnace and evacuate the furnace to a pressure below -0.01 MPa. Introduce Ar gas as a protective gas and set the flow rate to 1 L / min. Raise the temperature to 1050°C at a heating rate of 5-8°C / min. Then introduce methane and set the flow rate to 0.6 L / min, and the argon flow rate to 2.4 L / min. The ratio of methane to argon flow is 1:4. After keeping warm for 20 hours, cool with the furnace to obtain a dense C / CW composite material with a porosity of 22.55%.

[0040] Embodiment 5: The preparation method of the tungsten modified C / C composite material in this embodiment includes the following steps: S1: Weigh W powder and anhydrous ethanol in a weight ratio of 3:10 and place them in a beaker. Stir with a magnetic stirrer at room temperature for 1 h to form a suspension. S2: The density is 1.0 g / cm 3 The C / C composite material was cleaned by ultrasonic cleaning and dried in an oven at 80 °C for 10 h; S3: Build a vacuum filtration device and place the dried sample from S2 (xy side facing up) on the filter membrane. Use a pipette to extract the slurry and drip it onto the surface of the sample, controlling the powder to be evenly distributed on the surface. Continue until no more W powder can be drawn onto the surface. Remove the sample, rinse off the remaining powder on the surface with anhydrous ethanol, and weigh it after drying in an oven at 80°C for 10 h.

[0041] S4: Repeat step S3 until the weight gain of the sample is no longer obvious.

[0042] S5: Fix the composite material obtained in S4 in the mold of a small chemical vapor deposition furnace. Place the mold in the furnace and evacuate it to a pressure below -0.01 MPa. Introduce Ar gas as a protective gas and set the flow rate to 1 L / min. Raise the temperature to 1030°C at a heating rate of 5-8°C / min. Then introduce methane and set the flow rate to 0.6 L / min, and the argon flow rate to 2.4 L / min. The ratio of methane to argon flow is 1:4. After keeping warm for 30 hours, cool with the furnace to obtain a dense C / CW composite material with a porosity of 24.15%.

[0043] Comparative Example 1: This comparative example includes the following process: The other conditions of this comparative example are the same as those of Example 1, except that the density of S2 is 1.4 g / cm 3 C / C composite materials. Due to its low porosity and small pores, it is impossible to introduce 3-5μm W powder into the substrate surface to form a coating. Figure 5 As shown in Figure 5, the depth of W in the C / C composite matrix is ​​only 40 μm and cannot form a continuous W layer.

[0044] Comparative Example 2: This comparative example includes the following process: The other conditions of this comparative example are the same as those of Example 2, except that in S5, the temperature of the small chemical vapor deposition furnace is raised to 950 o C, carbon precipitation for 20 h. The porosity of the obtained sample was measured by the Archimedes drainage method to be 37.33%, and the density was low, indicating that the carbon precipitation effect was poor at this temperature.

[0045] Comparative Example 3: This comparative example includes the following process: The other conditions of this comparative example are the same as those of Example 2, except that in S5, the temperature of the small chemical vapor deposition furnace is raised to 1100 o C, carbon precipitation for 20 hours. Figure 6As shown, part of the metal W on the surface of the sample has reacted with the matrix C to form WC.

[0046] It can be seen from the results of the above examples and comparative examples that to prepare the C / CW composite material, a material having a density of 1.0-1.3 g / cm 3 The C / C composite material of the present invention is filtered to obtain the first composite structure. The C / C composite material within this density range has more pores, which can provide space for the introduction of W powder. In the chemical vapor infiltration process, an appropriate temperature range is required to control the efficiency of depositing pyrolytic carbon to be as high as possible and avoid chemical reaction between a large amount of W and C, so as to ensure that the W element exists in the form of metal inside the C / C composite material. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0047] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a tungsten-modified C / C composite material, characterized in that: The process includes the following: The C / C composite material is placed on a filter membrane, and the suspension of tungsten powder is filtered to obtain a first composite structure of tungsten powder and the C / C composite material, and the first composite structure is dried; The dried first composite structure is subjected to carbon deposition densification to obtain a tungsten-modified C / C composite material.

2. The method for preparing a tungsten-modified C / C composite material according to claim 1, characterized in that: During the filtration, the suspension is filtered out each time until no more suspension can be drawn into the surface of the C / C composite material, and then the mixture is dried.

3. The method for preparing a tungsten-modified C / C composite material according to claim 2, characterized in that: It also includes the following processes: The process of placing the dried first composite structure on the filter membrane, filtering the suspension of tungsten powder and drying the first composite structure is repeated until the first composite structure no longer increases in weight.

4. The method for preparing a tungsten-modified C / C composite material according to claim 2, characterized in that: Before drying the first composite structure composed of tungsten powder and C / C composite material, the residual powder on the surface of the first composite structure is washed away with anhydrous ethanol, and then dried.

5. The method for preparing a tungsten-modified C / C composite material according to claim 1, characterized in that: When performing suction filtration, the mesh layer and the non-woven fabric layer of the C / C composite material are arranged alternately with the surface facing upward.

6. The method for preparing a tungsten-modified C / C composite material according to claim 1, characterized in that: In the suspension of tungsten powder, the solvent is anhydrous ethanol, and the mass ratio of tungsten powder to anhydrous ethanol is 1: (3-4). When the first composite structure is dried, the drying temperature is 70-80° C. and the drying time is 10-12 h.

7. The method for preparing a tungsten-modified C / C composite material according to claim 1, characterized in that: The particle size of tungsten powder is 3-5 μm, and the density of C / C composite material is 1.0-1.3 g / cm 3 .

8. The method for preparing a tungsten-modified C / C composite material according to claim 1, characterized in that: The process also includes the following steps: pre-treating the C / C composite material by washing, and filtering the pre-treated C / C composite material by suction; When the C / C composite material is subjected to cleaning pretreatment, the C / C composite material is subjected to ultrasonic cleaning and then dried at 60-80° C. for 10-12 hours.

9. The method for preparing a tungsten-modified C / C composite material according to claim 1, characterized in that: The process of carbonizing and densifying the dried first composite structure includes: In a protective atmosphere, using methane gas, vapor-depositing pyrolytic carbon on the surface of the dried first composite structure to achieve carbon deposition and densification of the first composite structure; The temperature during vapor deposition of pyrolytic carbon is 1030-1070°C for 20-30 hours. After the deposition is completed, the temperature is first lowered to 300°C and then cooled with the furnace.

10. A tungsten modified C / C composite material, characterized in that: The tungsten-modified C / C composite material is prepared by the preparation method described in any one of claims 1-9.

Citation Information

Patent Citations

  • Preparation method of carbon / carbon-copper composite material

    CN102776404A

  • Preparation method of C / C-MoSi2 composite material

    CN105732123A

  • Preparation method of high-thermal-conductivity carbon / carbon-copper composite material

    CN105887059A

  • W-type barium ferrite / carbonyl iron composite waved absorbing silicon sheet and production method thereof

    CN107365135A

  • Catalyst-loaded graphene / single-walled carbon nanotube composite flexible electrode, preparation method and application

    CN116130671A